2014
DOI: 10.1016/j.devcel.2014.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Uniformity of Nucleosome Preservation Pattern in Mammalian Sperm and Its Connection to Repetitive DNA Elements

Abstract: Nucleosome-to-protamine exchange during mammalian spermiogenesis is essential for compaction and protection of paternal DNA. It is interesting that, depending on the species, 1% to 15% of nucleosomes are retained, but the generalizability and biological function of this retention are unknown. Here, we show concordantly in human and bovine that nucleosomes remained in sperm chromatin predominantly within distal intergenic regions and introns and associated with centromere repeats and retrotransposons (LINE1 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
184
2
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 137 publications
(201 citation statements)
references
References 50 publications
(59 reference statements)
13
184
2
2
Order By: Relevance
“…In the first human dataset (17) the retention prevalence of developmental promoters over the gene poor regions was suggested. Later, a study that utilized fixed chromatin and a smaller amount of micrococcal nuclease concluded that there is a prevalence of the gene-poor regions in the nucleosome fractions (19,20). A careful inspection of the latter datasets from human and bovine sperm nucleosome retaining regions still shows a limited number of promoters present corresponding to genes of signal transduction, protein processing and ATP-binding, suggesting their role in the early zygote development (20).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In the first human dataset (17) the retention prevalence of developmental promoters over the gene poor regions was suggested. Later, a study that utilized fixed chromatin and a smaller amount of micrococcal nuclease concluded that there is a prevalence of the gene-poor regions in the nucleosome fractions (19,20). A careful inspection of the latter datasets from human and bovine sperm nucleosome retaining regions still shows a limited number of promoters present corresponding to genes of signal transduction, protein processing and ATP-binding, suggesting their role in the early zygote development (20).…”
Section: Discussionmentioning
confidence: 99%
“…Later, a study that utilized fixed chromatin and a smaller amount of micrococcal nuclease concluded that there is a prevalence of the gene-poor regions in the nucleosome fractions (19,20). A careful inspection of the latter datasets from human and bovine sperm nucleosome retaining regions still shows a limited number of promoters present corresponding to genes of signal transduction, protein processing and ATP-binding, suggesting their role in the early zygote development (20). Furthermore, the overlap between human and bovine data showed the significant enrichment in genes associated with signal transduction and RNA and protein processing factors and suggests the conservative mechanism of nucleosome retention (20).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations